Las quintas y el teatro: una farsa macabra - Marie Salgues (Mélanges de la Casa de Velázquez)
Through an analysis of several plays from the period of the Sexenio Democrático, all revolving around the quintas [conscription], this article dissects the discours en acte and the differences between the voices of Barcelona and Madrid, between the positions of the politicians and the positions of the “independent” dramatists, between those committed to the system and those who for various reasons stood on its margins.